Network flow programming (NFP) model for syariah-compliant transfer of Islamic inheritances / Noraini Noordin - Noordin, Noraini (2017)
The absence of Syariah Court (SC) from the new IIT system has promoted the development of a Syariah-compliant Islamic inheritance transfer (IIT) system for inheritance at Small Estates Distribution Units (SEDUs) using Theory of Inventive Problem Solving (TRIZ). This system is capable of differentiating claim activity path followed by Islamic estates from non-Islamic estates. Ignorance of Islamic inheritance laws and claim procedures among Muslims has attributed to claim delays. Order and precedence relations in the modified TRIZ IIT system became the basis to establish a flow guideline network model for more effective IIT management (i.e. time and cost saving) at SEDUs or SCs. No quantitative approach using the shortest path algorithm has ever been applied to solve the delays in claim activities.